Analysis Of Differences in Dpk, Npl, And Roa in Rural Banks Before and After Cooperation with Financial Technology Companies - Nariswari Aliftahea Jasmine; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine the differences in the financial performance of Rural Banks (BPR) before and after collaborating with a Financial Technology (Fintech) company. The study was conducted on conventional BPRs in East Java that have partnered with the Fintech company KOMUNAL, which is registered with the Financial Services Authority (OJK). KOMUNAL is a P2P lending platform that connects promising SMEs with funding providers. The sampling technique used was purposive sampling, with a total sample of 33 BPRs. The data collected were analyzed using the Wilcoxon signed-rank test with a significance level of 5%. The results show that there is a significant difference in Third-Party Funds (DPK) before and after the collaboration with the Fintech company. However, no significant difference was found in Non-Performing Loans (NPL) between the periods before and after the collaboration. Additionally, the study found a significant difference in Return on Assets (ROA) before and after collaborating with Fintech. These findings indicate that collaboration with Fintech can improve DPK and ROA but have no impact on NPL.